If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(h + 10) = 110 Reorder the terms: 10(10 + h) = 110 (10 * 10 + h * 10) = 110 (100 + 10h) = 110 Solving 100 + 10h = 110 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-100' to each side of the equation. 100 + -100 + 10h = 110 + -100 Combine like terms: 100 + -100 = 0 0 + 10h = 110 + -100 10h = 110 + -100 Combine like terms: 110 + -100 = 10 10h = 10 Divide each side by '10'. h = 1 Simplifying h = 1
| 6ln(5x+4)=22 | | 5n+6-3n=-18 | | 7-3x=x-8+4x | | 4x+20/4= | | 4x^3+7x^2-20x-35=0 | | 5n-3n=-18 | | 6x+1=2x+5 | | 0=-x^2-19x-18 | | 50-18=4(x-3) | | 7-21g/7= | | 14x-262=5x-10 | | -(3-3a)=3(a-11) | | x=w^2-v^2 | | 5x^3-30x^2+25x= | | x^3-9x^2+22x-10=0 | | 14-8x=170-36x | | 0=6x^2+24x+2 | | 15c(2c-5)= | | -2(7+5b)+3(2b-3)= | | 2x+x-11+-7x=15 | | -136-8x=170-36x | | G(x)=-x^2-19x-18 | | -12m+8=-13m | | 19=7m+5(3-m) | | 2x-45=6 | | w^2=x+v^2 | | 7(6x+2)= | | x^2-45=20 | | (6c-5)+8(3c+4)= | | 12(3x+6)= | | -2(-2)(-3)(-4)-5= | | 6g=24-2(3+3g) |